2019
DOI: 10.1039/c8ce01877d
|View full text |Cite
|
Sign up to set email alerts
|

Wheel-and-axle topology-driven halogen bonds: formation of ladder, 1D and 2D networks in hexa-coordinated Sn(iv) porphyrins

Abstract: Wheel-and-axle topology-driven halogen bonded supramolecular networks in six-coordinated Sn(iv)-porphyrins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 40 publications
4
22
0
Order By: Relevance
“…A subsequent analysis indicated that only 3 structures (11% of the data set) exhibit type I interactions, while 17 structures (63% of the data set) exhibit type II interactions. Notably, 1 porphyrin structure (CSD code KIWTIW; Figure a) was found to exhibit both type I and type II interactions, straddling both sets. The geometry of the I···I motifs in the remaining 8 structures could not be interpreted as representing either type I or type II interactions; consequently, these were classified as contacts (Figure S10 and Table S13).…”
Section: Resultsmentioning
confidence: 99%
“…A subsequent analysis indicated that only 3 structures (11% of the data set) exhibit type I interactions, while 17 structures (63% of the data set) exhibit type II interactions. Notably, 1 porphyrin structure (CSD code KIWTIW; Figure a) was found to exhibit both type I and type II interactions, straddling both sets. The geometry of the I···I motifs in the remaining 8 structures could not be interpreted as representing either type I or type II interactions; consequently, these were classified as contacts (Figure S10 and Table S13).…”
Section: Resultsmentioning
confidence: 99%
“…In our previous work on six coordinated tin-porphyrin complexes, [29][30][31] we observed an interesting phenomenon in the solid phase. The location of the halogen bond donor or acceptor on the porphyrin plays a critical role in the self-assembly process.…”
mentioning
confidence: 89%
“…44,45 Similarly, replacing I-atoms with Br-atoms at the axial linkers led for the formation of type I XB interactions. 30 From these two examples it is clear that axial halogen atoms are either reluctant to participate in XB interactions altogether or participate in type I XB interactions due to a decrease in the potential of the σ-hole. Type I XB interactions are not truly considered an attractive contact (two electropositive regions of halogens (δ+) are in short contact and can form due to crystal packing), whereas type II is more attractive in nature (the electropositive region (δ+) of one halogen is in direct contact with electronegative region (δ-) of the other which provides a stabilizing electrostatic interaction).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the usual halogen bonding such as I⋅⋅⋅O, I⋅⋅⋅N, I⋅⋅⋅π and I⋅⋅⋅I, rare I⋅⋅⋅S bonds were also found for the first time. This idea was further explored in metalloporphyrin complexes by Patra and co‐workers through a ‘wheel and axle’ model comprising of a series of Sn(axial‐L) 2 −(5,10,15,20‐tetraiodoporphyrin) Sn IV TIPP(L) 2 , where L= halogen/nitro‐substituted benzoate moiety] derivatives (Figure 23C) [113] . In this design, the wheel comprised of the porphyrin unit, with the meso ‐phenyl position occupied by two pairs of iodine atoms.…”
Section: Halogen Bonded Supramolecular Polymers and Materialsmentioning
confidence: 99%